Artificial Neural Network in Virtual Reality : A Survey - Sharma, G.; Chandra, Sushil; Venkatraman, Saraynya; Mittal, Alok; Singh, Vijander (International Journal of Virtual Reality, 2016)
Virtual reality (VR) is defined as a 3-dimensional (3D), artificially simulated environment which allows the user to immerse himself/herself in it. From rehabilitation to data visualization, VR has been found to have many profound applications over the past decade or so. The addition of a suitable interface (e.g: haptics) is necessary in order to improve the quality of interaction with VR. Artificial Neural Network (ANN), a learning algorithm [i.e., a mathematical representation of any form of biological activity], which is one of the most widely adopted algorithms, is used for maintaining the properties of virtual reality (i.e., Immersivity and Interactivity). The primary objective of this review is to explore the limitless possibilities through the integration of ANN and VR. In addition to this, it also highlights the fact that an incumbent association of VR and ANN can lead to the construction of a highly interactive and immersive module in virtual reality.